2017
DOI: 10.1111/hae.13194
|View full text |Cite
|
Sign up to set email alerts
|

A prevalent CTLA4 missense variant significantly associates with inhibitor development in Argentine patients with severe haemophilia A

Abstract: Haemophilia A (HA) (OMIM #306700), an X-linked recessive disorder characterized by reduced activity of coagulation factor VIII (FVIII:C), is caused by deleterious mutations in the F8. HA can be treated by administration of the deficient FVIII. However, about 20%-30% of severe HA patients (biochemically defined as FVIII:C < 1 IU/dL) developed FVIII neutralizing antibodies (inhibitors) making replacement therapy ineffective. Inhibitors result in higher therapy costs and decreased quality-of-life and life expecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 14 publications
4
7
0
Order By: Relevance
“…These observations from our population closely agree with the inhibitor risks estimated from the literature (Garagiola, Palla, & Peyvandi, 2018;Marchione et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These observations from our population closely agree with the inhibitor risks estimated from the literature (Garagiola, Palla, & Peyvandi, 2018;Marchione et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…The phenotypic features associated with these large F8-deletions, particularly those involving more than one exon, show the upmost clinical severity including the highest predisposition to develop inhibitory antibodies against the therapeutic FVIII (odds ratio [OR; 95% confidence interval]: 7.07 [2.20-22.71], p < .0005; Marchione et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…15,16,27 The CTLA-4-318 C/T SNP in the promoter region –318 bp from the ATG start codon is associated with increased promoter activity, increased protein expression, a negative effect on the immune response, and hence a lower risk of inhibitor formation. 28,29 In the present study, we found no significant protective correlation between inhibitor formation and the –318 T allele in patients with either severe or mild/moderate HA, similar to the findings reported in an Indian study, 30 a Chinese cohort, 31 and a Brazilian study, 32 but in contrast to MIBS and Argentinean cohorts 9,12 that identified a substantial protective correlation between CTLA-4-318 C/T and inhibitor formation. It is noteworthy that most previous reports included only patients with severe HA.…”
Section: Discussionsupporting
confidence: 90%
“…911 Human genetic data support the hypothesis that predisposing factors associated with autosomal genes, including those mentioned above, are ethnically divergent and thus not constant among populations worldwide. 12…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation